Post-exercise hypotension: the effects of epanolol or atenolol on some hormonal and cardiovascular variables in hypertensive men. - Wilcox, R G (1987)
1 Eight men with primary hypertension were treated for 3 weeks with placebo, epanolol (200 mg or 400 mg), or atenolol 100 mg in a randomised cross-over study. Each active treatment period was preceded by a 3 week placebo treatment period and both investigators and subjects were blind to the active drug sequence. 2 At the end of each period, measurements were made of resting cardiovascular (heart rate, blood pressure, forearm blood flow) and biochemical variables (plasma renin, angiotensin II, aldosterone, adrenaline, noradrenaline, vasopressin, sodium and potassium concentrations and osmolality). Responses to exercise (including gas exchange, sweat rate, and ratings of perceived exertion) and the reflex cardiovascular adjustments to distal body subatmospheric pressure were also assessed. 3 The reduction of exercise-induced tachycardia by epanolol 400 mg was comparable to that of atenolol. There was very little difference in the effects of atenolol or epanolol 400 mg on resting blood pressure, but in both cases blood pressures were usually significantly lower than with epanolol 200 mg. 4 Although each active treatment influenced the renin-angiotensin system and circulating levels of catecholamines, the exercise-induced reduction in blood pressure was unaffected. Thus, the hypotensive effects of pharmacological and non-pharmacological interventions were additive.